2016
DOI: 10.1111/psyp.12686
|View full text |Cite
|
Sign up to set email alerts
|

Self‐referential processing in adolescents: Stability of behavioral and ERP markers

Abstract: The self-referential encoding task (SRET)—an implicit measure of self-schema—has been used widely to probe cognitive biases associated with depression, including among adolescents. However, research testing the stability of behavioral and electrocortical effects is sparse. Therefore, the current study sought to evaluate the stability of behavioral markers and event-related potentials (ERP) elicited from the SRET over time in healthy, female adolescents (n = 31). At baseline, participants were administered a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 29 publications
6
67
3
Order By: Relevance
“…Studies have shown strong correlations between endorsement of negative (but not positive) words and depressive symptoms (e.g., Disner, Shumake, & Beevers, 2016); increased endorsement of negative words (and decreased endorsement of positive words) on the SRET is also predictive of depression symptom course (Disner et al, 2016; Connolly, Abramson, & Alloy, 2015). Responses on the SRET also appear to be consistent over time particularly when depression symptoms remain relatively stable (Goldstein, Hayden, & Klein, 2015; Auerbach et al, 2016). …”
mentioning
confidence: 82%
“…Studies have shown strong correlations between endorsement of negative (but not positive) words and depressive symptoms (e.g., Disner, Shumake, & Beevers, 2016); increased endorsement of negative words (and decreased endorsement of positive words) on the SRET is also predictive of depression symptom course (Disner et al, 2016; Connolly, Abramson, & Alloy, 2015). Responses on the SRET also appear to be consistent over time particularly when depression symptoms remain relatively stable (Goldstein, Hayden, & Klein, 2015; Auerbach et al, 2016). …”
mentioning
confidence: 82%
“…The LPP is a slow-wave event-related potential (ERP) sensitive to emotional arousal that reflects elaborated attention toward affective stimuli (Auerbach, Stanton, Proudfit, & Pizzagalli, 2015; Auerbach et al, 2016; Hajcak, Weinberg, MacNamara, & Foti, 2012). The LPP is larger following unpleasant and pleasant stimuli compared to neutral stimuli (Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000; Schupp et al, 2000 Foti & Hajcak, 2008; Foti, Hajcak, & Dien, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nor were over-sampling procedures employed to make use of clinically depressed participants, although a number of participants in all three samples did endorse elevated depressive symptoms as noted in Table 2. However, many studies have utilized the SRET with nonclinical samples (e.g., Goldstein et al, 2015;Auerbach et al, 2016;Hayden et al, 2013), implying its effectiveness as a dimensional measure of self-referent processing in depression, and our samples are similar in makeup to these studies. Measures of socioeconomic status were not collected and thus cannot be reported.…”
Section: Discussionmentioning
confidence: 67%
“…Researchers also showed consistent endorsements of negative information when tested six months apart, which were only consistent for participants who remained depressed (Dozois & Dobson, 2001). Additionally, researchers who have examined the psychometrics of the SRET within study samples have shown high internal consistency in the responses (Auerbach et al, 2016). However, these studies all had relatively small samples (ns < 100) and internal reliability has not been routinely assessed with the SRET.…”
Section: Introductionmentioning
confidence: 99%